Estudo da eletroxidação de CO e metanol sobre eletrodos multicamadas metálicas Ptpc/Rh/Pt - Silva, Camila Daiane Ferreira da (2014)
Fuel cell is an alternative studied in recent years for energy conversion. A problem of this type of device is the choice of anode material and fuel used. Thus, different materials have been proposed besides the pure metals, such as alloys and metallic multilayers, and the direct conversion cell using small organic molecules has received particular attention. In this work we developed metallic multilayer Ptpc/Rh/Pt materials for the electroxidation of methanol and carbon monoxide. The technique used for the characterization of the electrodes and also to study the electroxidation of methanol and carbon monoxide was cyclic voltammetry. In addition, electrochemical impedance spectroscopy (EIS) was used in order to characterize the oxidation of methanol on these multilayers. The methanol electroxidation showed an onset potencial shifted towards more negative potencials over Ptpc/Rh/Pt and the peak current density increased about 283% over Ptpc/Rh2.0/Pt1.0 compared to Ptpc. EIS data indicated a lower resistance to charge transfer in the reactions performed on multilayers. Carbon monoxide electroxidation showed a higher current density for all multilayers electrodes when compared to Ptpc.